KUALITAS PELAYANAN KESEHATAN PADA PENYINTAS THALASEMIA DI KOTA SUKABUMI - Robila, Tiana; Amirulloh, M Rijal; Sampurna, Rizki Hegia (Kebijakan : Jurnal Ilmu Administrasi, 2024)
This study aims to determine the quality of health services for Thalassemia survivors in Sukabumi City. This study uses a qualitative research method with a narrative approach. The results of this study indicate that the Quality of Health Services for Thalassemia Survivors in Sukabumi City, especially at Rs. Bhayangkara Setukpa Sukabumi already has the following improvements: 1) Already has a special room for Thalassemia Survivors; 2) The chelation medicine already has various types of iron syrup, tablets, and brewed chelation medicine; 3) Have a special Thalassemia officer. As for when viewed based on the assessment of the dimensions of Reliability (Reliability), Responsiviness (Response/responsiveness), and Empathy (Empathy) health services provided by the apparatus/officers for Thalassemia Survivors are of high quality, but the dimensions of Tangibles (Intangible) and Assurance (Guarantee) are not qualified. or still not optimal, because the quality of health services provided is still not in accordance with the medical standards as outlined in the Regulation of the Minister of Health of the Republic of Indonesia Number 1109/MENKES/PER/VI/2011 concerning Technical Instructions for Guaranteed Thalassemia Treatment Services, especially in facilities and infrastructure. . The Sukabumi City Health Office provides a policy regarding the Health Services for Thalassemia Survivors in Sukabumi City, namely Thalassemia survivors participating in the National Health Insurance for the Healthy Indonesia Card (JKN KIS) do not need to go to the First Level Health Facility (FKTP) again to get referrals, and Thalassemia Sukabumi City has a halfway house as form of local government attention.